Financial Incentives for Pediatric HIV Testing in Kenya. Issue 11 (November 2018) - Njuguna, Irene N.; Wagner, Anjuli D.; Omondi, Vincent O.; Otieno, Verlinda A.; Neary, Jillian; Bosire, Rose; Babigumira, Joseph B.; Levin, Carol; Maleche-Obimbo, Elizabeth; Wamalwa, Dalton C.; John-Stewart, Grace; Slyker, Jennifer
Abstract : The acceptability of financial incentives for pediatric HIV testing was evaluated in Kenya. Sixty HIV-positive women with children of unknown status were randomized to receive 5, 10 or 15 conditional upon HIV testing. Forty-four (73%) completed child testing, with similar rates across arms. Uptake was significantly higher than a cohort with similar procedures but no incentives (73% vs. 14%, P < 0.001).